MADRASAH EDUCATION IN A SHIFTING EDUCATIONAL LANDSCAPE: NAVIGATING ADAPTATION, CONFRONTING CHALLENGES, ANDEXPLORING PROSPECTS FOR SUSTAINABLE DEVELOPMENT - Zain Fuadi Muhammad Roziqi Fath; Muqarramah Sulaiman Kurdi; Fenni Kurniawati Ardah; Abdul Wahab Syakhrani; Ansori (Adisam Publisher, 2023)
In our comprehensive study,